Biblioedukasi dan Animasi Edukasi; Meningkatkan Kompetensi Guru Sekolah Inklusi pada Kelompok Kerja Guru SD di Kabupaten Sigi [Biblioeducation and Educational Animation: Enhancing Competence of Inclusive School Teachers in the Primary School Teacher Working Group in Sigi Regency] - Muthia Aryuni; Nur Halifah; Ade Nurul Izatti G Yotolembah (Indonesia Berdaya, 2026)
Inclusive education requires teachers who are able to identify diverse learning needs, design adaptive instruction, and utilize engaging learning media that support all students, including those with special educational needs. The needs assessment conducted in the Sigi district showed that most teachers had not previously received comprehensive training on inclusive practices, and more than seventy percent lacked access to simple educational media such as story-based materials and animations. This community engagement program aimed to strengthen teacher competence through training on the development and classroom application of biblioeducation and educational animation grounded in local Kaili cultural values. Using a participatory training and mentoring approach, the program included workshops, hands-on media production, classroom implementation, and structured evaluation. Quantitative findings indicated substantial improvement in teacher competence, with the average pre-test score increasing from 64.67 to 90.50 in the post-test. More than eighty percent of teachers achieved medium to high gain scores, and sixty percent reported high levels of perceived competence after the training. Classroom observations also showed that the stories and animations developed effectively supported the delivery of empathy, cooperation, and anti-bullying values. These results demonstrate that integrating culturally grounded biblioeducation and educational animation is an effective strategy for enhancing inclusive teaching practices, especially in schools with limited resources. Abstrak. Pendidikan inklusif membutuhkan guru yang mampu mengidentifikasi kebutuhan belajar yang beragam, merancang pembelajaran yang adaptif, serta memanfaatkan media pembelajaran yang menarik untuk mendukung semua siswa, termasuk mereka yang memiliki kebutuhan pendidikan khusus. Penilaian kebutuhan yang dilakukan di Kabupaten Sigi menunjukkan bahwa sebagian besar guru belum pernah menerima pelatihan komprehensif tentang praktik inklusif, dan lebih dari tujuh puluh persen tidak memiliki akses ke media edukasi sederhana seperti materi berbasis cerita dan animasi. Program pengabdian masyarakat ini bertujuan untuk memperkuat kompetensi guru melalui pelatihan pengembangan dan penerapan biblioedukasi serta animasi edukasi yang berlandaskan nilai budaya lokal Kaili. Dengan pendekatan pelatihan partisipatif dan pendampingan, program ini meliputi lokakarya, produksi media secara langsung, penerapan di kelas, dan evaluasi terstruktur. Temuan kuantitatif menunjukkan peningkatan signifikan dalam kompetensi guru, dengan rata-rata skor pre-test meningkat dari 64,67 menjadi 90,50 pada post-test. Lebih dari delapan puluh persen guru mencapai skor peningkatan sedang hingga tinggi, dan enam puluh persen melaporkan tingkat kompetensi yang tinggi setelah pelatihan. Observasi kelas juga menunjukkan bahwa cerita dan animasi yang dikembangkan efektif mendukung penyampaian nilai empati, kerja sama, dan anti-perundungan. Hasil ini menunjukkan bahwa integrasi biblioedukasi dan animasi edukasi yang berlandaskan budaya lokal merupakan strategi efektif untuk meningkatkan praktik pengajaran inklusif, terutama di sekolah dengan sumber daya terbatas.